The Relationship Between Physical and Psychological Discomfort on the Quality of Life of Pregnant Women - Dita Erwinda; Misrawati Misrawati; Stephanie Dwi Guna (CV. Rayyan Dwi Bharata, 2024)
Pregnancy is a period when a pregnant woman needs to adapt with the physical and psychological change. During the pregnancy, the mother who cannot adapt with that change will experience discomfort and impact the life quality. This research aimed to find out the correlation between the physical and psychological discomfort and life quality of the pregnant women in the work area of Umban Sari Community Health Center. This research used descriptive correlational design by employing cross sectional approach. The research samples were 92 respondents that were selected by using purposive sampling technique. This research used Maternal Physical Discomfort Scale (MPDS), Depression Anxiety Stres Scale (DASS-21), and World Health Organization Quality Of Life-BREF (WHOQOL-BREF). The analysis used was bivariate analysis by using chi-square test. The research results showed that there was a significant correlation between the physical discomfort and the life quality of pregnant women and the research results also showed that there was a significant correlation between the life quality of pregnant women.